The Route to European Hegemony : India's Intra-Asian Trade in the Early Modern Period (Sixteenth to Eighteenth Centuries) - Maloni, Ruby. (Abingdon : Routledge, 2021)
"The advent of the Europeans was crucial in transforming the contours of Maritime Asia. The commercial situation in the Indian Ocean was impacted in many ways over the longue duree from the sixteenth to the eighteenth centuries. To offset the adverse balance of trade and to maximize profits, the Europeans imposed their own coercive and monopolistic systems along the existing trade routes. Systematic exploitation of economic opportunities in Asia by Europeans began with the coming of the Portuguese, followed by other European maritime powers. It culminated with Britannia ruling the Asian waters with warships and a strong merchant marine. A study of the operational and ideological motivations that propelled the European powers'activities in the Indian Ocean can help to construct a coherent interpretation of the foundations of empire that were being laid, at first insidiously and later, aggressively. This book analyses the mechanism and implications of Europe's sustained engagement in Intra-Asian trade which is as an essential context to the establishment of colonial empires."--Publisher description
1. Politico-Economic Ramifications of Europe's Intra-Asian Trade -- 2. Indian Maritime Centres: Foreland and Hinterland -- 3. Indian Merchants and Institutional Structures: Resilience and Resistance -- 4. European Merchants at Indian Ports: Contest for Profit Maximization -- 5. The English East India Company: Commercial Power and Dominance.
OCLC-licensed vendor bibliographic record.
Keywords: Trade routes -- Asia; Trade routes -- Europe; International trade -- History -- 16th century; International trade -- History -- 17th century; International trade -- History -- 18th century; Europe -- Commerce -- Asia; Asia -- Commerce -- Europe; HISTORY / Asia / India & South Asia; HISTORY / Modern / 16th Century; HISTORY / Modern / 18th Century